1933 Tex. Gen. Laws 219-20, 1st Called Sess., An Act Defining “Machine Gun” and “Person”; Making It an Offense to Possess or Use Machine Guns. . . , ch. 82, §§ 1-4, 6 - (:unkn) unknown (General Publisher, 1933)
Prohibited possession of a machine gun; punishable by imprisonment up to 10 years. Prohibited selling, leasing, giving, bartering, exchanging, or trading a machine gun; punishable by imprisonment for 2 months to 10 years.
--
Keywords: MACHINE GUN RESTRICTION